Tools for High Performance Computing 2009 Proceedings of the 3rd International Workshop on Parallel Tools for High Performance Computing, September 2009, ZIH, Dresden - Müller, Matthias S.; Resch, Michael M.; Schulz, Alexander; Nagel, Wolfgang E. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
As more and more hardware platforms support parallelism, parallel programming is gaining momentum. Applications can only leverage the performance of multi-core processors or graphics processing units if they are able to split a problem into smaller ones that can be solved in parallel. The challenges emerging from the development of parallel applications have led to the development of a great number of tools for debugging, performance analysis and other tasks. The proceedings of the 3rd International Workshop on Parallel Tools for High Performance Computing provide a technical overview in order to help engineers, developers and computer scientists decide which tools are best suited to enhancing their current development processes.